New records of Bulbophyllum in the Flora of Vietnam - Truong, Vuong Ba (Universidad de Costa Rica, 2020)
Bulbophyllum leysianum (sect. Hyalosema) and B. ovalifolium (sect. Macrocaulia) are recorded as new for the flora of Vietnam. Both species originate from the Hon Ba Nature Reserve (Khanh Hoa Province, Vietnam). The first was found as an epiphyte on fallen branch in riparian lowland forest, while the second was recorded on small branches in a canopy tree at about 1500 m a.s.l.